A multicenter cross-sectional study on the prevalence of overactive bladder and its impacts on the quality of life in gynecologic outpatients - Do Young Kim; Da Hae Jang; Hyun Jin Kim; Sa Ra Lee; Myung Jae Jeon; Jung-Ho Shin; Hee Dong Chae (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveThe present study assessed the prevalence of overactive bladder (OAB) symptoms in gynecologic outpatients and the effects of OAB on a patient's quality of life.MethodsThe survey was completed by adult female patients who visited the gynecology clinic for examination or treatment of gynecologic conditions. The subjects who met the exclusion criteria were excluded. The survey included a questionnaire assessing general characteristics, the purpose of the visit, diagnosis, and the presence or absence of OAB. The subjects were asked whether they were under medical treatment for OAB symptoms, and the degree of discomfort in daily activities was evaluated.ResultsIn total, 1,990 female subjects visiting the gynecology clinics of 4 different institutions were recruited. On OAB Symptom Score, 188 subjects responded with scores of ≥2 for question #3 (≥1 time(s) weekly). The severity of OAB symptoms was as follows: 345 subjects had mild OAB, 127 subjects had moderate OAB, and 12 subjects had severe OAB. The prevalence of OAB symptoms was 10.30%.ConclusionThe present study confirmed that OAB symptoms are common, with a prevalence of 10.30%. Patients with OAB symptoms frequently neglect to seek medical intervention. Our findings will help inform patients to recognize their condition and seek medical assistance, especially in gynecologic outpatient clinics.